Procedure Text Writing Skills Using Silent Film Media In Grade Vii Students Of State Junior High School 10 South Tangerang - Nisah, Ainun; Jatoi, Qammar-Un_Nisa; Tleumuratov, Genjemurat (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study examines the effectiveness of silent film media in improving the procedure text writing skills of Grade VII students at State Junior High School 10 South Tangerang. Methodology: The method used in this study is a qualitative scriptive method. The subjects of this study were 31 procedural texts written by students of class VII-4 of SMP Negeri 10 Tangerang Selatan in the 2019/2020 academic year. Data collection techniques in this study were observation, tests, interviews, and documentation. Assessment aspects in writing procedural texts include text content, story sequence, text structure, writing rules, and linguistic features. Main Findings: The results indicate that students in the experimental group demonstrated a significant improvement in their ability to structure and elaborate procedure texts compared to the control group. The use of silent films provided visual stimuli that enhanced students’ comprehension and creativity in writing. Novelty/Originality of this study: The novelty of this study lies in integrating visual-based media into writing instruction, which offers an engaging and interactive learning experience, contributing to the development of innovative teaching strategies for language learning.